Long‐term regulation of signalling components of adenylyl cyclase and mitogen‐activated protein kinase in the pre‐frontal cortex of human opiate addicts - Ferrer‐Alcón, M.; J. García‐Fuster, M.; La Harpe, R; García‐Sevilla, J. A. (Journal of neurochemistry, 2004)
Opiate addiction involves the development of chronic adaptive changes in µ‐opioid receptors and associated pathways (e.g. cAMP signalling) which lead to neuronal plasticity in the brain. This study assessed the status of cAMP and mitogen‐activated protein kinase (MAPK) pathways in brains (pre‐frontal cortex) of chronic opiate addicts. In these subjects (n = 24), the immunodensities of adenylyl cyclase‐I, PKA Cα, total and phosphorylated CREB were not different from those in sex‐, age‐ and PMD‐matched controls. Moreover, the ratio pCREB/tCREB was similar in opiate addicts (0.74) and controls (0.76), further indicating that opiate addiction in humans is not associated with an upregulation of several key components of cAMP signalling in the pre‐frontal cortex. In contrast, the components of MAPK cascade (Ras/c‐Raf‐1/MEK/ERK) were decreased in the same brains. Notably, pronounced downregulations of phosphorylated MEK (85%) and ERK1/2 (pERK1: 81%; pERK2: 80%) were quantitated in brains of opiate addicts. Chronic morphine treatment in rats (10–100 mg/kg for 5 days) was also associated with decreases of pERK1/2 (59–68%) in the cortex. In SH‐SY5Y cells, morphine also stimulated the activity of pERK1/2 (2.5‐fold) and the MEK inhibitor PD98059 blocked this effect (90%). The abnormalities of MAPK signalling might have important consequences in the long term development of various forms of neural plasticity associated with opiate addiction in humans.